The other Kuala Lumpur living in the shadows of a globalising Southeast Asian city - Lepawsky, Josh 1972- (Routledge Malaysian studies series, 2014)
"Kuala Lumpur, like many Southeast Asian cities, has changed very significantly in recent decades--expanding its size, "modernising" and "globalising". For many people these changes represent "progress". This book, however, focuses on the more marginalised sections of society, especially those people whose lives have been adversely affected by recent changes. It considers how the everyday lives of the marginalised in society have been affected by recent changes, showing how urban renewal, the law, and Malay nationalism and Islamicisation often work against many of these marginal groups, and examining how they struggle to survive"--Provided by publisher.